Error analysis in a learner corpus : a study of errors amongst Grade 12 Oshiwambo speaking learners of English in northern Namibia - Nghikembua, Annelie Ndapanda (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2015)
High failure rates in English as a second language at secondary school level have become a concern in the Namibian education sector. From 2005 until 2013, the overall performance of the grade 12 learners in English as a second language on Ordinary level in the Oshana region was unsatisfactory. In fact, only a minority (18.52 percent) of the grade 12 learners obtained a grading in the range of A to D in comparison to the majority (81.48 percent) of learners who obtained a grading of E to U. The poor performance was attributed to: poor sentence structure, syllabification and spelling (Directorate of National Examination and Assessment, 2007-2010). The causes of these low performance rates however, were not scientifically explored in this region. Therefore this study embarked on an investigation in order to identify the reasons behind the low performance rates of the grade 12 Oshiwambo speaking learners of English and to determine whether the impressionistic results from the Directorate's report correlate with the present study's findings. In order to understand the dynamic linguistic system of the learners, a contrastive analysis of Oshiwambo and English was done in order to investigate the potential origins of some of the errors. An error analysis approach was also used to identify, classify and interpret the non-standard forms produced by the learners in their written work. Based on the results obtained from this study, a more comprehensible assessment rubric was devised to help identify learners' written errors. A group of 100 learners from five different schools in the Oshana region was asked to write an essay of 150 to 200 words in English. The essays were analysed using Corder's (1967) conceptual framework which outlines the steps that a researcher uses when undertaking an error analysis study. The errors were categorised according to Keshavarz's (2006) linguistic error taxonomy. Based on this taxonomy, the results revealed that learners largely made errors in the following categories: phonology/orthography, morpho-syntax, lexico-semantics, discourse and techniquepunctuation. The study concluded that these errors were most likely due to: first language interference, overgeneralisation, ignorance of rule restriction and carelessness. Other proposed probable causes were context of learning and lack of knowledge of English grammar. The study makes a significant contribution, in that the findings can be used as a guide for the Namibian Ministry of Education in improving the status quo at schools and informing the line Ministry on various methods of dealing with language difficulties faced by learners. The findings can also empower teachers to help learners with difficulties in English language learning, thereby enabling learners to improve their English language proficiency. The study has proposed methods of intervention in order to facilitate the teaching of English as a second language in the Oshana region. In addition, the study has devised an easily applied assessment rubric that will assist in identifying non-standard forms of language used by learners. The reason for designing a new rubric is because the rubric which is currently being used is believed to be subjective, inconsistent and lacks transparency.,Name in Graduation Programme as: Nghikembua, Anneli Ndapanda
Keywords: Corpora (Linguistics); Language and languages -- Study and teaching -- Error analysis; English language -- Study and teaching (Secondary) -- Namibia -- Oshana; Second language acquisition; Contrastive linguistics